Modification of The Oil Cooler to Avoid Oil Leaking in Generator Transformer PLTU Labuan “Moderator” - Prima Galih Pratama; Setyawan Santoso; Shandy Helmi Ramadhan (Departemen Teknik Mesin dan Industri, Universitas Gadjah Mada, 2023)
The Main Generator Transformer for PLTU Labuan is a transformer with a power capacity of 350 MVA and a cooling system of 6 pcs OFAF (Oil Force Air Force) type. During operation, a disturbance to the Main Generator Transformer (GT) was caused by an oil cooler leak. This is caused by the corrosive expand tube caused by the constituent material consisting of 2 different types of materials. The oil leak caused environmental pollution, decreased oil level, and increased winding temperature and oil temperature on GT. During the decade of operation of the PLTU Labuan, GT oil cooler leaks almost always occur every year, both in unit 1 and unit 2. To anticipate this, we made modifications to the end tube design by changing the type of material on the expanded tube from initially using iron to aluminum such as tube material outside the expanded position. The next design change is to increase the length of the end tube which is equipped with the knock and glue with an expansion strength above normal operating temperature which makes the end tube more reliable by increasing the surface area attached to the body oil cooler. In addition to making changes to the design, this modification reuses used oil coolers that have good tube quality so that they can be reused with more reliable quality. By making these modifications, it can increase the readiness of generating unit production (EAF) by 3.33% in one MO event due to the replacement of the oil cooler generator transformer and lower maintenance costs for the required transformer oil cooler. The modified Oil Cooler was installed during the Maintenance Outage in Unit 1 and Overhaul unit 2 in 2021 and is still operating well for 20 months of operation.